Mekanisme dan Kinetika Kuesing Aloe Emodin terhadap Fotooksida Asan Linoleat - Yohana S. Kusuma Dewi; Tranggono Tranggono; Sri Raharjo; Pudji Hastuti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
To study the effects of methylene blue and aloe emodin on the photosensitized oxidation were prepared in methylene chloride systems. The oxidation of linoleic acid was determined by measuring the peroxide value. The quenching mechanism and kinetics of aloe emodin in methylene blue-sensitized photooxidation of linoleic acid were studied by the steady-state kinetic methods. The methylene blue consentration was produced signicantly increased of peroxide value on singlet oxygen oxydation of linoleic acid The effect of aloe emodin concentration on singlet oxygen oxidation of linoleic acid was produced signicantly decreased of peroxide value of linoleic acid.. The calculated quenching rate of aloe emodin was 4.68 x 109 11I1 S -1. Aloe emodin both of quenched singlet oxygen and sensitizer to reduce photosensitized oxidation of linoleic acid by the singlet oxygen quenching mechanism and the excited triplet oxygen sensitizer quenching mechanism. The ability of antiphotooxidant activity of aloe emodin was affected by concentration.